Distribution and Abundance of Blood Shells (Anadara granosa) on the Coast of Concong Luar Village Indragiri Hilir Regency - Fadhil, Mohd. Isfan; Mulyadi, Aras; Tanjung, Afrizal (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This study was conducted in September 2021, around the coastal of Concong luar village Indragiri Hilir Regency with the aim to find out the abundance, distribution, and morphometrics of blood shell (Anadara granosa). The method used survey methods, in which blood shell sampling and aquatic substrates, as well as measurements of environmental parameters, were conducted in the field and in the laboratory. Determination of sampling location by purposive sampling is based on the character of the environment in the location of the research. Based on the results of research that has been obtained an abundance value at the station 1 = 4,8 Ind/m2, station 2 = 8,7 Ind/m2, and station 3 = 3 Ind/m2. The pattern of blood shell levy in the waters of Concong Luar Village stations 1 and 2 is clustered, while station 3 is evenly distributed. Furthermore, the results of measurement of the width of the highest blood shells are 16 - 30 mm in 70 individuals, followed by size >31 mm in 43 individuals, the lowest measurement result is <15 mm in 27 individuals and the highest measurement of the length of the blood shells 16 – 30 mm of 77 ind, followed by a size >31 mm of 42 ind, and the lowest measurement result is <15 mm of 29 ind